2000
DOI: 10.1088/0022-3727/33/6/313
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We use the Jones matrix method to develop a numerical method which can be used to calculate the reflection of cholesteric liquid crystals. We derive the formula for the propagation of normally incident light in a cholesteric liquid crystal with multiple reflections taken into account. Using the derived formula, we numerically calculate the reflection spectra of the cholesteric liquid crystal under various conditions, and compare them with the results obtained using the Berreman 4 × 4 method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 13 publications
(16 reference statements)
2
21
0
Order By: Relevance
“…Comparing with the corresponding figures in Ref. [36], there is an excellent agreement between the improved Jones matrix method and our proposed mode-matching technique. The advantage of our method, as compared to the improved Jones matrix method presented in Ref.…”
Section: Numerical Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Comparing with the corresponding figures in Ref. [36], there is an excellent agreement between the improved Jones matrix method and our proposed mode-matching technique. The advantage of our method, as compared to the improved Jones matrix method presented in Ref.…”
Section: Numerical Resultssupporting
confidence: 74%
“…We considered the same exact cases investigated by Yang et al [36] in order to provide comparisons to our simulations. In their paper, they used the Jones matrix method to develop an improved numerical method where multiple reflections were taken into account.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The CLC material has been removed by dipping it into acetone to show the aperture dimensions. The film has a uniform thickness of approximately 5 m and a rms surface roughness of less than 0.5 m. Calculations by Yang et al 11 have shown that for a CLC material of a given handedness, close to maximum reflectance is obtained if the thickness of the CLC material between the electrodes is about ten times the pitch of the chiral nematic helix. For CLC materials that reflect visible light, a uniform thickness of approximately 5 m is most desirable for obtaining optimum brightness, in conjunction with high contrast ͑because of reduced backscattering͒ and low switching voltage.…”
Section: Single-substrate Cholesteric Liquid Crystal Displays By Collmentioning
confidence: 99%
“…To overcome the limitations, Berreman introduced the 464 matrix method accounting for multiple reflections and oblique incidence cases [6]. Later, extensions of the Jones matrix method were formulated to overcome multiple reflections [7], and oblique incidence cases [8]. In spite of these improvements, another major restriction remains in the matrix-type methods due to the assumption that the variation of the dielectric tensor occurs only along the direction of wave propagation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These methods are still valuable for LC display device applications when each individual pixel exceeds the extent of many optical wavelengths and there is a slow variation of LC orientation along the transverse directions [9]. Consequently, most applications of the matrix-type methods are one-dimensional problems in which the only allowed spatial variation is along the normal to the LC displays [8,[10][11][12]. However, a significant number of currently evolving LC display devices such as small-sized pixels for head-mounted displays, pixel edges, and multi-domain LC displays in which the pixel size becomes very small, the homogeneity along the pixel reduces, and domains with different director orientations can occur [13,14].…”
Section: Introductionmentioning
confidence: 99%